2008
DOI: 10.1111/j.1471-6712.2007.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

The hospital appropriateness evaluation protocol in elderly patients: a technique to evaluate admission and hospital stay

Abstract: AEP's high-reliability and moderate-validity results with regard to clinical judgement positions it as a useful instrument for appropriate hospitalization screening in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
2
18
0
1
Order By: Relevance
“…Consequently the rate of false negative could be underestimated. A second stage of this study could be to test the AEP criteria in the emergencies room [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently the rate of false negative could be underestimated. A second stage of this study could be to test the AEP criteria in the emergencies room [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The size of the sample was estimated assuming that 10% of the hospital admissions are inappropriate [ 16 ], with an accuracy of 0.02 and a reliability level of 95%. The required sample was of 863 files, plus a 20% considering the exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Our DoCS showed that the older patients were, the less likely they were to meet the criteria for acute care. When inpatients were grouped in 10-year age bands, it was found consistently that advancing age was associated with an increasing proportion not meeting the criteria (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although the appropriateness of hospital admissions, particularly in elderly people, has been extensively investigated and standardized tools have been proposed for clinical use, they are likely poorly implemented in the current clinical practice, at least in our region. [23][24][25][26] It appears likely that these inappropriate admissions reflect the absence of immediately available alternative settings of chronic care for these older ill patients.…”
Section: Discussionmentioning
confidence: 99%